Synthesis and Antitumor Activity of Some NewN1-(8-fluoro-4-oxoquinolin-5-yl)amidrazones - Yahya, Hind M. A.; Zahra, Jalal A.; Sabri, Salim S.; El-Abadelah, Mustafa M.; Bardaweel, Sanaa (Current Organic Synthesis, 2024)
Background: Hydrazonoyl chloride, accessible from the respective 5-amino-8-fluoro- 4-oxoquinoline-3-carboxylate, undergoes a reaction with sec-cyclic amines to generate N1-(1- ethyl-8-fluoro-4-oxoquinolin-5-yl)amidrazone carboxylates. Introduction: A novel set of N1-(1-ethyl-8-fluoro-4-oxoquinolin-5-yl)amidrazone carboxylates (7a-h) incorporating N-piperazines or related congeners was synthesized via interaction of the hydrazonoyl chloride (6), accessible from the respective 5-amino-8-fluoro-4-oxoquinoline-3-carboxylate, with the appropriate sec-cyclic amine. These new compounds were characterized by 1HNMR, 13C-NMR, and HRMS spectral data and screened for their anticancer activities. Aims: This study aimed at the synthesis of novel N1-( 4-oxoquinolin-5-yl)amidrazone carboxylate derivatives and investigated their potential as anticancer agents. Objective: The reaction of hydrazonoyl chloride with the appropriate sec-cyclic amine was applied to synthesize a novel set of N1-(1-ethyl-8-fluoro-4-oxoquinolin-5- yl)amidrazone carboxylates that incorporate N piperazines. Methods: A direct reaction of piperazines and related sec-cyclic amines with N-(4-oxoquinolin-5- yl)nitrile imine (1,3-dipole) was carried out for 8-10 h. Results: The 1,3-dipole, generated in situ from its hydrazonoyl chloride precursor in the presence of trimethylamine, is suitable for the facile synthesis of N1-(1-ethyl-8-fluoro-4-oxoquinolin-5- yl)amidrazone carboxylates. Conclusion: This study led to the successful synthesis of novel N1-(8-fluoro-4-oxoquinolin-5- yl)amidrazones. All the examined compounds showed moderate activity with reasonable IC50 values in the micromolar range compared to Doxorubicin.
Keywords: amidrazones